Trends in the practice environment of Chinese healthcare professionals from 2008 to 2023: an age period cohort analysis - Liangquan Lin; Yi Che; Jiaxin Zhou; Yixin Gui; Xinqing Zhang (BMC, 2024)
Abstract Background Healthcare practice environment plays a vital role in evaluation and the development of health sector in China. However, there are few comprehensive reviews and studies focusing on its state and changing trends. This study aimed to examine the dynamic trends in Chinese healthcare professionals' perceptions of their practice environment from 2008 to 2023 using age period cohort (APC) analysis. Methods Four national cross-sectional surveys of healthcare professionals were conducted in 2008, 2013, 2018, and 2023. APC analysis was performed to distinguish effects of age, period and cohort. Covariates like gender, department, job satisfaction, and doctor-patient relationships were also analyzed. Results Between 2008 and 2023, healthcare professionals' perceptions of their practice environment first declined and then improved. Those aged 28-38 during 2013-2018 and born between 1978 and 1988 had the most negative perceptions. After 2018, perceptions improved, peaking in 2023. Those under 23 and over 43 exhibited larger age effects. Birth cohorts after 1993 also had more positive effects. Controlling for covariates attenuated APC effects. Females, those in obstetrics and emergency medicine, nurses, technicians, and administrators perceived better environments. Higher job satisfaction and doctor-patient relationship harmony are also associated with more positive perceptions. Income matching efforts and perceptions of promotion fairness had positive impacts, while increasing severity of physical fatigue and psychological anxiety negatively influenced perceptions of the practice environment. Conclusions The APC analysis provided nuanced insights into evolving practitioner perceptions amid healthcare reforms in China. Tailored policies focused on career stage and generation are needed to address disruptions and sustain improvements. Monitoring feedback on reforms and changes is essential for optimizing the practice environment over time.